A canção tropicalista: um percurso crítico - Pedro Henrique Dutra Martins Rocha Elias (2015)
The present work proposes the study of the tropicalist song as an object of discussion and problematization of culture in Brazil. Based on the production of poet Oswald de Andrade, the tropicalists reinterpret the modernist devouring metaphor, paving the way for a rupture that managed to a) synchronize the Brazilian cultural production with the global scene and b) emphasize the importance of aesthetic efforts as critical procedures, and also as a political act. By the way, the intention of embracing syncretism and the contradictions that are intrinsic to the social formation of the country led Tropicália to the controversial field of culture industry. Adopting the mass media as part of a project, the tropicalists reinforce the debate on the possibility and the character of art in the scope of culture industry: the utopia of fine arts shared with the masses or the dystopia of creation tamed by market rules? This is the task which the present study is based on.